Die verhouding van die godsdienste tot mekaar. Hoër konsensus, godsdiensekumene en dialoog van nader bekijk. - Verster, P. (Acta Theologica, 2022)
In this article the problem of the relationship among religions is assessed. Specific models are discussed. Heinrich Ott stands for maximum consensus, Hans Küng for religious ecumenism and Dawid J Bosch for dialogue. These viewpoints are judged and it is shown that reconciliation is crucial to the relationship among religions. Similarities among religions do exist, because fa ith in a Supreme Being (Creator) is possible, but the true redemption lies in the fact that the heart is directed towards God the Trinity. Therefore all the religions are not on the same level next to one another, and thus the christian gospel should still be proclaimed.